Long term outcomes of 176 patients with X-linked hyper IgM syndrome treated with or without hematopoietic cell transplantation - de la Morena, M; Leonard, D; Torgerson, T; Cabral-Marques, O; Slatter, M; Aghamohammadi, A; Chandra, S; Murguia-Favela, L; Bonilla, F; Kanariou, M; Damrongwatanasuk, R; Kuo, C; et al. (Elsevier, 2016)
BACKGROUND: X-linked hyper IgM syndrome (XHIGM) is a primary immunodeficiency with high morbidity and mortality compared to normal individuals. Hematopoietic cell transplant (HCT) has been considered a curative therapy, but the procedure has inherent complications, and may not be available for all patients. OBJECTIVES: We sought to collect data on the clinical presentation, treatment, and follow-up of a large sample of patients with XHIGM in order to (1) compare long-term overall survival and general well-being of patients treated with or without HCT along with clinical factors associated with mortality, and (2) summarize clinical practice and risk factors in the subgroup of patients treated with HCT. METHODS: Physicians caring for patients with primary immunodeficiency diseases were identified through the Jeffrey Modell Foundation, United States Immunodeficiency Network, Latin American Society for Immunodeficiency, and the Primary Immune Deficiency Treatment Consortium. Data was collected using a REDCap web application. Survival from time of diagnosis or transplant was estimated using the Kaplan-Meier method, compared using log-rank tests, and modeled using proportional hazards regression. RESULTS: Twenty-eight clinical sites provided data on 189 patients diagnosed with XHIGM between 1964 and 2013; 176 had valid follow-up and vital status information. Sixty-seven patients (38%) received HCT. The average follow-up time was 8.5 ± 7.2 years (range: 0.1-36.2 years). No difference in overall survival was observed between patients treated with or without HCT (p=0.671). However, risk associated with HCT decreased for diagnosis years 1987-1995; the hazard ratio was significantly < 1 for diagnosis years 1995-1999. Liver disease was a significant predictor of overall survival [HR (95% CL): 4.9 (2.2, 10.8), p<0.001]. Among survivors, those treated with HCT had higher median Lansky and Karnofsky scores than those treated without HCT (p<0.001). Among patients receiving HCT, 27 (40%) developed graft versus host disease, and most deaths occurred within 1 year of transplant. CONCLUSION: No difference in survival was observed between patients treated with or without HCT across all diagnosis years 1964-2013. However, survivors treated with HCT experienced somewhat greater well-being and hazards associated with HCT decreased, reaching levels of significantly less risk, in the late 1990s. Among patients treated with HCT, treatment at an early age is associated with improved survival Optimism remains guarded as additional evidence accumulates.